2023
DOI: 10.1101/2023.05.08.539897
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolving spike-proteinN-glycosylation in SARS-CoV-2 variants

Abstract: It has been three years since SARS-CoV-2 emerged and the world plunged into a “once in a century” pandemic. Since then, multiple waves of infection have swept through the human population, led by variants that were able to evade any acquired immunity. The co-evolution of SARS-CoV-2 variants with human immunity provides an excellent opportunity to study the interaction between viral pathogens and their human hosts. The heavilyN-glycosylated spike-protein of SARS-CoV-2 plays a pivotal role in initiating infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 175 publications
1
14
0
Order By: Relevance
“…This is true no matter the differences in protein source, type of variants, MS techniques, and data processes used in these studies, presumably due to the relatively buried location of this residue . Using human-cell-expressed ectodomain S protein, many laboratories (including ours in this study) have determined that some other sequons, such as N61, N603, N709, N717, N801, and N1074, are heavily occupied by oligomannose-type glycans. ,,,,,, The fact that these residues are in the area between the head and the stalk of an S trimer structure might suggest that steric effects exist in these areas, preventing access of glycosylation enzymes. On the other hand, two recent reports have revealed that only N61 and N234 are almost fully modified by oligomannose glycans on the S variants investigated. , This might be because all of the proteins in these two studies were obtained from the same manufacturer.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This is true no matter the differences in protein source, type of variants, MS techniques, and data processes used in these studies, presumably due to the relatively buried location of this residue . Using human-cell-expressed ectodomain S protein, many laboratories (including ours in this study) have determined that some other sequons, such as N61, N603, N709, N717, N801, and N1074, are heavily occupied by oligomannose-type glycans. ,,,,,, The fact that these residues are in the area between the head and the stalk of an S trimer structure might suggest that steric effects exist in these areas, preventing access of glycosylation enzymes. On the other hand, two recent reports have revealed that only N61 and N234 are almost fully modified by oligomannose glycans on the S variants investigated. , This might be because all of the proteins in these two studies were obtained from the same manufacturer.…”
Section: Resultsmentioning
confidence: 84%
“…The S protein of the SARS-CoV-2 virus is heavily glycosylated with 22 potential N-glycosylation sites (sequons, Figure ) on each S protomer. These glycans can shield antigenic sites from immune surveillance, affecting viral neutralization and immune evasion strategies. Previous studies have also demonstrated that the glycans play other roles beyond shielding the S protein from host immune recognition. , Since the outbreak of the COVID-19 pandemic, the glycosylation profile of the SARS-CoV-2 S glycoproteins on the initial strain and evolving variants has been intensively studied, particularly through the use of advanced liquid chromatography coupled to tandem mass spectrometry (LC-MS) techniques ,, with recombinantly expressed proteins of ectodomain or subunit constructs and even viral derived S protein . The analysis of glycopeptides derived from S proteins allows the determination of N-glycan profiles for all 22 conserved sequons as well as two novel sequons in the Gamma spike protein.…”
mentioning
confidence: 99%
“…This is true no matter the differences in protein source, type of variants, MS techniques, and data processes used in these studies, presumably due to the relatively buried location of this residue (13). Using human-cell-expressed ectodomain S protein, many laboratories (including ours in this study) have determined that some other sequons, such as N61, N603, N709, N717, N801, and N1074, are heavily occupied by oligomannose-type glycans (14,25,26,30,31,39,41). The fact that these residues are in the area between the head and the stalk of an S trimer structure might suggest that steric effects exist in these areas, preventing the access of glycosylation enzymes.…”
Section: Characterization Of N-glycosylation On S Proteinsmentioning
confidence: 85%
“…Previous studies have also demonstrated that the glycans play other roles beyond shielding the S protein from host immune recognition (23,24). Since the outbreak of the COVID-19 pandemic, the glycosylation profile of the SARS-CoV-2 S glycoproteins on the initial strain and evolving variants has been intensively studied, particularly through the use of advanced liquid chromatography coupled to tandem mass spectrometry (LC-MS) techniques (20,23,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) with recombinantly expressed proteins of ectodomain or subunit constructs and even viral derived S protein (14). The analysis of glycopeptides derived from S proteins allows the determination of N-glycan profiles for all 22 conserved sequons as well as two novel sequons in Gamma spike protein.…”
Section: Introductionmentioning
confidence: 99%
“…To set a foundation for structure-function relationship, we set forth to characterize conserved structural elements among homologous constructs to distinguish species-specific and genus-specific features of SL5. Such comparative structural biology studies were indeed being widely pursued to assess the structures of multiple coronavirus spike proteins, including the SARS-CoV-2 spike protein with mutations (16) and cross-species (63)(64)(65)(66). Such tertiary structural comparisons in RNA-only structures, however, have been limited.…”
Section: Introductionmentioning
confidence: 99%